Towards a multilevel governance framework on the implementation of patient rights in health facilities: a protocol for a systematic scoping review - Bart Criel; Nora Engel; NS Prashanth; Sara Van Belle; Meena Putturaj; Anja Krumeich; Prakash B Nagendrappa (BMJ Open)
Introduction Patient rights are “those rights that are attributed to a person seeking healthcare”. Patient rights have implications for quality of healthcare and acts as a key accountability tool. It can galvanise structural improvements in the health system and reinforces ethical healthcare. States are duty bound to respect, protect and promote patient rights. The rhetoric on patient rights is burgeoning across the globe. With changing modes of governance arrangements, a number of state and non-state actors and institutions at various levels play a role in the design and implementation of (patient rights) policies. However, there is limited understanding on the multilevel institutional mechanisms for patient rights implementation in health facilities. We attempt to fill this gap by analysing the available scholarship on patient rights through a critical interpretive synthesis approach in a systematic scoping review.Methods The review question is ‘how do the multilevel actors, institutional structures, processes interact and influence the patient rights implementation in healthcare facilities? How do they work at what level and in which contexts?” Three databases PubMed, LexisNexis and Web of Science will be systematically searched until 30th April 2020, for empirical and non-empirical literature in English from both lower middle-income countries and high-income countries. Targeted search will be performed in grey literature and through citation and reference tracking of key records. Using the critical interpretive synthesis approach, a multilevel governance framework on the implementation of patient rights in health facilities which is grounded in the data will be developed.Ethics and dissemination The review uses published literature hence ethics approval is not required. The findings of the review will be published in a peer-reviewed journal.Registration number PROSPERO 2020 CRD42020176939